Mild Hypoxic–Ischemic Encephalopathy: Can Neurophysiological Monitoring Predict Unfavorable Neurological Outcome? A Systematic Review and Meta-analysis - Falsaperla, Raffaele; Sciuto, Sarah; Gioè, Daniela; Sciuto, Laura; Pisani, Francesco; Pavone, Piero; Ruggieri, Martino (American Journal of Perinatology, 2021)
Objective Hypoxic–ischemic encephalopathy (HIE) is the second cause of neonatal deaths and one of the main conditions responsible for long-term neurological disability. Contrary to past belief, children with mild HIE can also experience long-term neurological sequelae. The aim of this systematic review is to determine the predictive value of long-term neurological outcome of (electroencephalogram) EEG/amplitude-integrated electroencephalogram (aEEG) in children who complained mild HIE.Study Design From a first search on PubMed, Google Scholar, and clinicalTrials.gov databases, only five articles were considered suitable for this study review. A statistical meta-analysis with the evaluation of odds ratio was performed on three of these studies.Results No correlation was found between the characteristics of the electrical activity of the brain obtained through EEG/aEEG in infants with mild HIE and subsequent neurological involvement.Conclusion EEG/aEEG monitoring in infants with mild HIE cannot be considered a useful tool in predicting their neurodevelopmental outcome, and its use for this purpose is reported as barely reliable.Key Points
Keywords: mild; HIE; newborn; neurophysiological monitoring; neurological outcome